2017
DOI: 10.1016/j.pec.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making and goal-setting in chronic disease management: Baseline findings of a randomized controlled trial

Abstract: Objective Growing interest in collaborative goal-setting has raised questions. First, are patients making the ‘right choices’ from a biomedical perspective? Second, are patients and providers setting goals of appropriate difficulty? Finally, what types of support will patients need to accomplish their goals? We analyzed goals and action plans from a trial of collaborative goal-setting among 302 residents of a high-poverty urban region who had multiple chronic conditions. Methods Patients used a low-literacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…A recent systematic review of goal setting with patients who were older confirmed the need for studies to examine the effects of personalised care planning on goal attainment, ‘especially patient’s personal goals as opposed to goals determined by clinicians or researchers’ 27. Kangovi et al found that patients with chronic conditions from low socioeconomic groups thought broadly about their goals when encouraged to 28. Most published literature on goal setting suggests goals are often constrained or amended by the healthcare team, frequently clinically prioritised rather than patient prioritised, amended or constrained by the clinician, and reoriented to a biomedical focus,2931 and, in rehabilitation settings, there is evidence that patients may be ill prepared to play a more proactive role and therefore not have goals in mind 32…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of goal setting with patients who were older confirmed the need for studies to examine the effects of personalised care planning on goal attainment, ‘especially patient’s personal goals as opposed to goals determined by clinicians or researchers’ 27. Kangovi et al found that patients with chronic conditions from low socioeconomic groups thought broadly about their goals when encouraged to 28. Most published literature on goal setting suggests goals are often constrained or amended by the healthcare team, frequently clinically prioritised rather than patient prioritised, amended or constrained by the clinician, and reoriented to a biomedical focus,2931 and, in rehabilitation settings, there is evidence that patients may be ill prepared to play a more proactive role and therefore not have goals in mind 32…”
Section: Discussionmentioning
confidence: 99%
“…34,44 Given the skills and time required to listen to the patient narrative, calculate an individual risk profile, and communicate risk–benefit implications for each patient, the quality of decision support aids for medications to prevent stroke in patients with atrial fibrillation falls short. 45…”
Section: Discussionmentioning
confidence: 99%
“…34,44 Given the skills and time required to listen to the patient narrative, calculate an individual risk profile, and communicate risk-benefit implications for each patient, the quality of decision support aids for medications to prevent stroke in patients with atrial fibrillation falls short. 45 Patients' trust in providers' recommendations does not eliminate the need for patient involvement in decisionmaking. While providers were "reluctant to prescribe" OACs due to bleeding risk, patients reported a willingness to accept the bleeding risk and take OACs, if recommended.…”
Section: Provider Decision Aidsmentioning
confidence: 99%
“…Details of this trial have been previously described. 1618 Briefly, enrollment took place between July 2013 and October 2014 at two urban internal medicine clinics. Eligible patients lived in a high-poverty region and were diagnosed with two or more of the following chronic diseases: diabetes, obesity, hypertension or tobacco dependence.…”
Section: Methodsmentioning
confidence: 99%